The Influence of Leadership Style, Education and Training (Diklat) and Work Discipline on Perumdam Tirta Kencana Employee Performance, Samarinda City - Amelia Amelia; Annisa Wahyuni Arsyad (Eduvest - Journal of Universal Studies, 2024)
Training is an inseparable component in efforts to improve employee qualifications in an organization.  The purpose of this research is to determine the influence of leadership style, education and training (training), and work discipline on employee performance at Perumdam Tirta Kencana, Samarinda City. The type of research in this research is a descriptive quantitative and associative approach. Data collection techniques use observation, questionnaires, interviews, and documentation. With a sample size of 100 respondents from various levels of positions ranging from managers, and assistant managers to employees. In this study, the Proportionate Stratified Random Sampling technique was used, namely random sampling taking into account the existing strata. This means that each stratum is represented according to its proportions. The analysis technique in this research uses multiple linear regression analysis and is analyzed using SPSS version 29 software. The results of this research show that both leadership style, education and training (training), and work discipline partially have a significant positive effect on the performance of Perumdam Tirta Kencana Kota employees. Samarinda. Meanwhile, simultaneously the variables of leadership style, education and training (training), and work discipline have a significant effect on the performance of employees of Perumdam Tirta Kencana, Samarinda City with a significance level of less than 0.05 (0.000<0.05). The research results also show that the work discipline variable has the most dominant influence on employee performance with a β value of 0.451 and a significance value of less than 0.05 (0.000<0.05).